Photo Rechargeable Li‐Ion Batteries Using Nanorod Heterostructure Electrodes (Small 51/2021). Issue 51 (23rd December 2021) - Kumar, Amar; Thakur, Pallavi; Sharma, Rahul; Puthirath, Anand B.; Ajayan, Pulickel M.; Narayanan, Tharangattu N.
Abstract : Li‐Ion Batteries In article number 2105029, Tharangattu N. Narayanan and co‐workers show a single nanowire containing MoS2 /MoO x regions as a photo‐electrode for Li + ion batteries. This inorganic nanowire‐based two electrode solar battery can be highly stable in organic electrolytes while ensuring high lithium intercalation area and light–matter interaction volume. This opens up the potential for developing semiconductor heterostructures–based solar batteries where they can ensure stability and good photo‐efficiency.